Mengungkap Kondisi Kerang Darah (Anadara granosa) dan Kerang Kepah (Meretrix meretrix) di Pantai Batu Belubang, Pulau Bangka - Umroh umroh; La Ode Wahidin; Aditya Pamungkas; Agung Pryambada (Universitas Mataram, 2024)
Batu Belubang Beach has abundant biological resources of Darah Mussels (Anadara granosa) and Kepah Mussels (Meretrix meretrix) in season. On the other hand, Batu Belubang waters are a post-tin mining area, therefore it is a concern for people to consume shellfish from the area. This concern is caused by the results of previous studies that said that post-tin mining areas left heavy metals, one of which was non-essential heavy metals such as Pb and Cu. Therefore, this study aims to examine the heavy metal content of Cd and Pb in shellfish meat, and determine the condition of gill tissue and meat of Darah Mussels (Anadara granosa) and Kepah Mussels (Meretrix meretrix) from Batu Belubang. This research method is purposive sampling, and several analyses consisting of: analysis of heavy metals in sediment and meat, tissue observation from muscle/meat and gill histology. The results showed that the concentration of heavy metals Cd, Pb in sediment is still below the quality standard, this is due to the sediment texture at Batu Belubang Beach dominant with sand, so it has a low binding power to heavy metals. The concentration of heavy metals in meat is also still below quality standards, so it is still safe for consumption. This condition is also strengthened by the results of tissue observations that show the condition of the flesh and gill tissues has not been damaged. This condition shows that both shells have not experienced tissue disruption because the accumulation of heavy metals is still very low.